Pengaruh Value Added Intellectual Capital Terhadap Kinerja Keuangan BUMN20 Tahun 2019-2020 - Thalia Thalia; Francis Hutabarat (Faculty of Economics and Business, Universitas Klabat, 2022)
The purpose of this research is to find out the impact of company’s value added intellectual capital from 2019-2020. This research used quantitative approach, which using numeral data and descriptive statistics. The sample of this research utilizes “BUMN20 - company’s index” that reported financial statement from 2019-2020 and It has a positive outcome in terms of the profit. The result of this research will be tested whether it is significant or not. When the ‘f’ value is below its confidence level (5%) we can conclude that Value Added Human Capital (VAHU), Structural Capital Value (STVA), and Value Added Capital Employed (VACA) has a significant effect towards financial performance of BUMN20 firm. Partially, this research found out the significant test of ‘t’ VACA is 0.006 which there is a significant relationship between VACA and financial performance of BUMN20 firm. On the contrary, this research shows that the variables of VAHU and STVA have no significant impact between VAHU and financial performanxe and the same way about the relationship between STVA and financial performance of BUMN20. Keywords: Financial Performance, Structural Capital Value, Value-Added Intellectual Capital, Value-Added Capital Employed, Value-Added Human Capital. Tujuan penelitian ini adalah untuk mengetahui pengaruh value added intellectual capital perusahaan bumn pada tahun pengamatan 2019-2020. Penelitian ini menggunakan pendekatan kuantitatif dimana penelitian ini menggunakan data berbentuk angka serta merupakan suatu penelitian statistik deskriptif. Sampel penelitian menggunakan perusahaan index BUMN20 yang menerbitkan laporan keuangan 2 tahun berturut-turut dalam 2019-2020 dan memiliki laba bersih positif selama periode pengamatan. Hasil penleitian ini menunjukan bahwa secara simultan nilai dari signifikansi uji f sebesar 0.046 < 0.05 yang berarti value added human capital (VAHU), structural capital value added (STVA), dan value added capital employed (VACA) berpengaruh secara signifikan terhadap kinerja keuangan perusahaan BUMN20. Secara parsial didapati bahwa nilai signifikan uji t VACA 0.006 yang berarti adanya pengaruh signifikan antara VACA dengan kinerja keuangan pada perusahaan BUMN20. Sebaliknya, penelitian ini menunjukan bahwa untuk variabel VAHU dan STVA didapati bahwa tidak ada pengaruh signifikan antara VAHU dengan kinerja keuangan dan juga STVA dengan kinerja keuangan perusahaan BUMN20. Kata kunci: Kinerja Keuangan, Structural Capital Value Value-Added Intellectual Capital, Value-Added Capital Employed,,Value-Added Human Capital.